2020
DOI: 10.1111/nph.16994
|View full text |Cite
|
Sign up to set email alerts
|

Multiple stressors drive convergent evolution of performance properties in marine macrophytes

Abstract: Extreme environments have driven the evolution of some of the most inspiring adaptations in nature. In the intertidal zone of wave-swept shores, organisms face physical forces comparable to hurricanes and must further endure thermal and desiccation stress during low tides, compromising their physiological and biomechanical performance. We examine how these multiple stressors have influenced the evolution of tissue properties during desiccation using eight phylogenetically independent pairs of intertidal and su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 68 publications
0
2
0
Order By: Relevance
“…The intertidal zone exposes inhabitants to challenging environmental conditions (Carrington, 1990; Demes et al, 2021; Gracey et al, 2008; Neumann, 1976). Particularly, intertidal macrophytes face excessive solar irradiance (Li et al, 2014; Unsworth et al, 2012) and mechanical stress from wave impacts (Carrington, 1990; Demes et al, 2021). Our initial experiment confirmed that irradiance could influence C. okamurae 's phenotype.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The intertidal zone exposes inhabitants to challenging environmental conditions (Carrington, 1990; Demes et al, 2021; Gracey et al, 2008; Neumann, 1976). Particularly, intertidal macrophytes face excessive solar irradiance (Li et al, 2014; Unsworth et al, 2012) and mechanical stress from wave impacts (Carrington, 1990; Demes et al, 2021). Our initial experiment confirmed that irradiance could influence C. okamurae 's phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…Caulerpa okamurae's natural habitat is the intertidal zone, which poses extreme environmental conditions for its inhabitants. Particularly, macrophytes on rocky shores are exposed to wave-induced mechanical stress (Carrington, 1990;Demes et al, 2021). Therefore, we conducted culture experiments to investigate the effects of artificial water flow, which generates mechanical stress on C. okamurae's morphology.…”
Section: Experimental Validation Of Hydrodynamic Effects On Phenotypi...mentioning
confidence: 99%